Biodegradation of gamma-sterilised biomedical polyolefins under composting and fungal culture environments - Alariqi, Sameh A. S.; Kumar, A. P.; Rao, B. S. M.; Singh, R. P. (Polymer Degradation and Stability, 2006)
Polyolefin-based commodities are widely used as biomedical devices and food packaging after gamma-sterilisation. The aim of the present work was to study the effect of gamma-sterilisation on the biodegradation of polyolefins. Films of isotactic polypropylene, high-density polyethylene and ethylene-propylene (EP) copolymers were sterilised under gamma-radiation with doses of 10 and 25 kGy. Neat and sterilised samples were incubated in compost and fungal culture environments. The changes in functional groups, surface morphology and chain scission in polymer chains were characterized by FTIR spectroscopy, SEM and viscometric measurements, respectively. A gradual decrease in intrinsic viscosity [eta] and increase in carbonyl and hydroxyl regions in FTIR spectra were found for the gamma-sterilised samples as a function of increasing dose. Polypropylene was found to be more susceptible to both radio-oxidation and biodegradation. It was observed that in case of ethylene-propylene copolymers, extent of gamma-sterilisation and/or biodegradation depends on the composition and distribution of comonomers. Important surface erosion was detected by SEM, for higher sterilisation doses, after composting. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: Biodegradation; chain scission; Composting and fungal culture; gamma-sterilisation; Polyolefins